Prinsip Ketauhidan dalam Perspektif Maqasid al-Quran: Analisis Ayat-Ayat Perintah, Larangan, dan Mukammil - Muhammad Khairul Mukminin; Mely Bilqisti Aula (LPPM IIQ An Nur Yogyakarta, 2026)
The principle of monotheism (tawhid) serves as the primary foundation of Islamic teachings and constitutes the essence of all maq??id al-Qur’an. This study is motivated by the importance of understanding how the Qur’an emphasizes the value of tawhid through verses of command, prohibition, and mukammil verses that function to perfect meaning. The aim of this research is to reveal that the entire structure of the Qur’anic teachings is oriented toward the purification of tawhid and the development of correct faith as the basis for shaping human behavior and social order. The methodology employed is qualitative research based on library studies with a maq??id? exegesis approach, which analyzes the meaning of verses contextually based on kontemporer and modern tafsir such as al-Ta?r?r wa al-Tanw?r by Ibn ‘?sh?r, fi Zhilalil Qur’an by Sayyid Qutb, Tafsir al-Mishbah by Quraish Shihab. The results indicate that the Qur’anic verses of command and prohibition serve to affirm the oneness of Allah and prevent humans from all forms of polytheism, while mukammil verses, such as the stories of the prophets, promises, and threats, strengthen the values of tawhid through moral and spiritual approaches. The contribution of this study lies in reinforcing the understanding that tawhid is not merely a theological aspect but also encompasses ethical and social dimensions that shape human personality and civilization. In conclusion, the principle of tawhid represents the highest maq??id in the Qur’an, integrating faith, worship, and morality, and serves as the foundation for achieving happiness in this world and the hereafter.